(untitled) (Ius Novum, 2021)
The article aims to present the concept of the obligation to have counsel for the defence, to characterise it in the light of the doctrine and case law, and to determine its function and justification in the Polish criminal procedure. Moreover, the paper describes institutions that are subject to the obligation laid down both in Criminal Procedure Code and special acts. The articlediscusses problems concerning the obligation to have counsel for the defence, draws specialattention to the fact that counsel can on their own develop motions concerning their own cases that are subject to the obligation, and suggests amendments to criminal procedure law.